Increasing English teachers' innovation through training on teaching modules development with digital technology integration - Yuli Astutik; Sheila Agustina; Fika Megawati; Rishma Anggraini (Universitas Muhammadiyah Malang, 2023)
In order to achieve quality learning in accordance with the aspirations and the fourth goal of SDGs, teachers need to create learning that is complete and in accordance with the needs of students. This complete and appropriate learning can be demonstrated by the teaching modules used by the teacher. In fact, teachers still encounter problems in compiling teaching modules that suit the needs of students in the current era of digital technology. This obstacle is also experienced by high school English teachers in Sidoarjo. One of the challenges is the lack of innovation in using and implementing information and technology-based English learning media. Therefore, with this community service, the authors aim to increase the high school English teachers' innovation through training on teaching module development with EdPuzzle integration. The success of this program was measured from a questionnaire filled out by the teachers. As a result, teachers who previously did not know what EdPuzzle was were finally able to create and implement it in class. They argue that digital media such as EdPuzzle is very useful for teaching and learning English. Thus, this community service has been carried out properly and succeeded in achieving the planned goals.